Family and personal factors predisposing adolescents to substance abuse in high-risk urban areas - María Quinde Reyes; Francisco Jiménez Bautista; Nadia Soria-Miranda; Daniel Oleas; Guido Mascialino; Isaac Vera Ponce; Jose A. Rodas (PLoS ONE, 2025)
Objective This study explored the influence of personal and familial factors on adolescent substance abuse in high-risk urban areas. The aim was to identify psychological and family-based predictors of abuse to inform more comprehensive prevention strategies. Method A comparative cross-sectional design was applied to a sample of 60 adolescents aged 12–18 from vulnerable neighbourhoods in Guayaquil, Ecuador. Participants were divided into two groups: those with substance use disorder (SUD) and those who did not use drugs at all. Emotional stability and cognitive control were assessed using the Cuestionario de Personalidad Situacional, while family dynamics were evaluated with the McMaster Family Assessment Device and the Risk Family Characteristics Inventory. Welch’s t-tests and chi-square analyses were conducted for group comparisons, and multivariate logistic regression identified predictors of drug abuse. Results Both groups demonstrated below-average scores in cognitive control and emotional stability, with substance abuse participants showing significantly lower cognitive control. Contrary to expectations, overall family functioning did not significantly differ between groups. However, adolescents with substance abuse were more likely to have family members with substance abuse issues. Logistic regression revealed that critical health problems in the family, poor family problem-solving abilities, and low emotional stability were significant predictors of drug abuse, with respective odds ratios indicating increased risk. Conclusion The findings underscore that adolescent substance abuse is shaped by both individual psychological vulnerabilities and specific family stressors, rather than by global family functioning alone. Effective interventions should integrate support for emotional regulation with family-based strategies that enhance problem-solving and address critical health burdens. These results suggest a need to reframe prevention approaches to target both personal and environmental risk mechanisms simultaneously. While the study’s cross-sectional nature and reliance on self-reports limit causal inferences, its findings provide valuable direction for future longitudinal and intervention-based research.